2013
DOI: 10.1016/j.neulet.2013.04.056
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB activity is inversely correlated to RNF11 expression in Parkinson's disease

Abstract: RING finger protein 11 (RNF11), a negative regulator of NF-κB signaling pathway, colocalizes with α-synuclein and is sequestered in Lewy bodies in Parkinson’s disease (PD). Since persistent NF-κB activation is reported in PD, in this report we investigated if RNF11 expression level is correlated to activated NF-κB in PD. We examined RNF11 expression levels in correlation to phospho-p65, a marker for activated NF-κB, in control and PD brain tissue from cerebral cortex. In addition we performed double immunofluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…The pro‐inflammatory cytokines secreted by microglia cells such as IL‐1β and TNF‐α may directly bind to cytokine receptors that locate on the surface of DA neurons, thereby triggering the activation of NF‐κB, eventually leading to DA neuron degeneration through apoptotic cell death (Phani, Loike, & Przedborski, ). Notably, NF‐κB expression is highly elevated in brain samples from PD patients (Pranski et al, ). Based on in vitro studies, it has been found that NF‐κB activation is triggered by MPP + in BV‐2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The pro‐inflammatory cytokines secreted by microglia cells such as IL‐1β and TNF‐α may directly bind to cytokine receptors that locate on the surface of DA neurons, thereby triggering the activation of NF‐κB, eventually leading to DA neuron degeneration through apoptotic cell death (Phani, Loike, & Przedborski, ). Notably, NF‐κB expression is highly elevated in brain samples from PD patients (Pranski et al, ). Based on in vitro studies, it has been found that NF‐κB activation is triggered by MPP + in BV‐2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced production of free radicals is a major determinant in the transcriptional activation of nuclear factor kappa B (NFkB). p65 subunit (p65) is the main constituent protein and a marker for the nuclear factor kappa B (NFkB), which is considered the master transcriptional regulator of the inflammatory process and is associated with the neurodegenerative mechanism in animal models induced by 6‐OHDA and other neurotoxins such as rotenone and MPTP . Moreover, NFkB up‐regulates the transcription of several genes, including interleukin‐1β (IL‐1β) and inducible nitric oxide synthase (iNOS) .…”
Section: Discussionmentioning
confidence: 99%
“…Pyrrolidine dithiocarbamate (PDTC), another NF-κB inhibitor, significantly ameliorated the DA deficits induced by MPTP in wild-type mice, where MPTP treatment significantly increased oxidative damage. Consistently, PDTC significantly attenuated MPTP-induced behavioral impairments in wild-type mice (124). Activated NF-κB expression levels were significantly increased in the striatum of MPTP-treated PD mouse models (125).…”
Section: Transcriptional Regulation Of Inflammatory Processesmentioning
confidence: 91%